Case report of distal gastrectomy applied in primary duodenal bulb adenocarcinoma - Xiang, Jin; Li, Yuan; Zheng, Biao; Yi, Qingqun (Frontiers in Surgery, 2025)
IntroductionPrimary duodenal bulb adenocarcinoma (PDA) is a rare and aggressive malignancy, frequently misdiagnosed due to its nonspecific clinical presentation and the lack of reliable biomarkers. While pancreaticoduodenectomy (PD) remains the standard radical treatment, its high complication rates have prompted the search for alternative therapeutic strategies.MethodsWe report the case of a 51-year-old male presenting with recurrent gastrointestinal bleeding and severe anemia, initially misdiagnosed as a benign duodenal bulb ulcer perforation. After conservative management failed, the patient underwent laparoscopic distal gastrectomy with gastrojejunostomy. Postoperative pathological examination confirmed poorly differentiated adenocarcinoma (pT4N1M0) with intact mismatch repair proteins (MLH1/MSH2/MSH6/PMS2+). The patient completed 8 cycles of CapeOX chemotherapy and remained disease-free for 3 years.ResultsThis case highlights the diagnostic challenges associated with ulcer-mimicking PDA of the duodenal bulb. Distal gastrectomy achieved complete tumor resection with acceptable morbidity, suggesting its potential as a viable alternative to PD in carefully selected cases. The combination of surgical resection and CapeOX chemotherapy yielded favorable outcomes, although long-term efficacy requires further validation.DiscussionClinicians should consider the possibility of malignant transformation in cases of medically refractory duodenal bulb ulcers. Distal gastrectomy combined with adjuvant chemotherapy may represent a feasible treatment option for locally advanced PDA, underscoring the need for additional studies to clarify its role in therapeutic algorithms.